Addressing Loneliness in Dementia Patient’s Caregiver Through Spiritual Aspect - Christophorus Aditya Pawitan; Agustina Konginan (Faculty of Medicine, Universitas Airlangga, 2024)
Introduction: In this brief case report, we aim to focus on the spiritual aspect and how it may benefit in addressing loneliness. Case: The case is a female 62 years old, diagnosed with generalized anxiety disorder with a psychosocial stressor of perceived isolation (loneliness), treatment approach consists of medication and spiritual-integrated cognitive behavioral therapy focused on her loneliness. Discussion: According to the definition spirituality is related to a transcendental being (vertical) and relation with others, the environment, and oneself (horizontal). In loneliness, the psychosocial symptom of perceived social isolation might be caused by the falling apart of a spiritual relation, either vertical or horizontal. Conclusion: Loneliness might be prolonged by a change in spiritual value and addressing loneliness through a spiritual aspect is an area that needs to be explored in future studies. Keywords: Spirituality, Loneliness, Spiritual Intervention, Caregiver, Mental Health